MAKNA SELIBAT BAKTI MENURUT TEOLOGI TUBUH YOHANES PAULUS II - Gregorius Hertanto Dwi Wibowo; Marianus Ada (Pineleng Theological Review, 2026)
In light of the rising cases of sexual deviance today, the meaning of consecrated celibacy is frequently questioned and often regarded as contrary to human nature. Furthermore, the declining appreciation for the value of the human body triggers a need for a positive theological foundation for understanding consecrated celibacy. Utilizing a literature study method, the authors intend to examine Pope John Paul II's thoughts on celibacy within his Theology of the Body (TOB). The research results indicate that celibacy is not a rejection of sexuality, but rather a voluntary choice for the sake of the Kingdom of Heaven, rooted in the "nuptial meaning of the body"—a natural orientation to love and give of oneself. By exploring original experiences (solitude, unity, and nakedness), celibacy is shown as a concrete expression that God is the fulfillment of man's deepest longings. Eschatologically, celibacy serves as an anticipatory sign of eternal life, where humanity achieves perfect union with God after the resurrection of the body. This study offers a new perspective for discussions on celibacy by positively integrating sexual desire. It affirms celibacy as an actualization of human identity as the image of God, capable of total love without sexual relations. Consequently, celibacy is viewed as a noble path for human nature.